THE ROLE OF SOCIAL MEDIA AS A BUSINESS COMMUNICATION TOOLIN IMPROVING CUSTOMER LOYALTY - Muh. Husriadi; Bunga Kartika; Nada Kusuma (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
rapid development of social media has made this platform a tool main business communication, but many business actors face challenges in utilizing social media to increase loyalty customers. This study aims to examine the role of social media as a tool business communication in building and improving loyalty customers. The method used is qualitative with a case study approach, involving interview in-depth and observation of active business actors utilizing social media. Research results show that selecting platforms such as Instagram and WhatsApp, a personal and responsive communication strategy, and appropriate management of challenges and risks significantly contribute to increased engagement. loyalty customers. Implications In practice, this research emphasizes importance dynamic digital communication strategy adaptation and risk management communication on social media to strengthen business- customer relationship continuously . This research contributes to the development of theory digital business communications and offers directions strategic for business practices in the digital age